Legal order in the world's oceans : UN Convention on the Law of the Sea - Nordquist, Myron H.; Moore, John Norton, 1937-; Long, Ronán J. (Center for Oceans Law and Policy (Series) ;, 2017)
Legal Order in the World's Oceans: UN Convention on the Law of the Sea assesses the impact of the 1982 Convention on the Law of the Sea (UNCLOS) and many aspects and challenges of modern law of the sea. --